Drug Related Problems in Pediatric Patients: A Pharmacist Led Prospective Interventional Study - Inamdar, Syed Zia; Londhe, Sushil Kumar; Abdul, Hadi; Rakshit, Patil; Mallanagouda, Patil (Indian Journal of Pharmacy Practice)
Drug-Related Problems (DRPs) are common in hospitalized pediatric patients and may adversely affect therapeutic outcomes. The present study aimed to assess the prevalence and pattern of DRPs in pediatric inpatients and to evaluate the role of pharmacist-led interventions in optimizing drug therapy. A six-month prospective interventional study was conducted in the pediatric inpatient department of a tertiary care hospital. Clinical pharmacists reviewed patient medication profiles and identified DRPs using the Pharmaceutical Care Network Europe (PCNE) classification system. A total of 115 patients were included, of whom 87 (75.65%) experienced at least one DRPs, accounting for 165 DRPs. Drug choice problems (48.48%) were most frequent, followed by drug interactions (30.90%) and dosing problems (7.87%). Pharmacist interventions were proposed for 115 DRPs, primarily at the prescriber level (47.27%). The mean number of DRPs per patient was 1.89±1.3. The study highlights the critical role of clinical pharmacists in identifying and managing DRPs and improving medication safety in pediatric patients.
Keywords: Adverse drug reaction; Drug Interaction; Drug-related problems; PCNE Classification; Pediatrics; Pharmaceutical care; Interventions